2012
DOI: 10.4236/ns.2012.45042
|View full text |Cite
|
Sign up to set email alerts
|

Major-minor element analysis in some plant seeds consumed as feed in Turkey

Abstract: In this study, samples (clover, oats, bean, green lentil, spinach, corn, red lentil and rice) taken from some seeds consumed as food by people and from plant seeds used as provender are examined. Element analysis (Al, B, Ba, Bi, Ca, Cd, Co, Cr, Cu, Fe, K, La, Mg, Mn, Na, Ni, Pb, Sn, Sr, Sb, Si, Ti, U, Zn and Zr) in these samples was measured by using ICP-OES. Ca, K and Mg as major elements in all samples are determined. As results of the element analysis, meaningful relations between the elements in seeds have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
2
12
1
Order By: Relevance
“…Fe 16.5-146 mg/kg, Cr 0.17-1.72 mg/kg, Mn 0.52-3.98 mg/kg, Co 0.34-0.76 mg/kg and Ni ND are all in the above ranges. In fact the level of Fe in this study is in a higher range (16.5-146 mg/kg), compared to only one literature [17] from Turkey 159 mg/kg. The high value of Fe in this study is most probably resulted from the high concentration of Fe in the soil.…”
Section: Comparison Of Metal Levels Of the Present Study With Literatcontrasting
confidence: 74%
See 2 more Smart Citations
“…Fe 16.5-146 mg/kg, Cr 0.17-1.72 mg/kg, Mn 0.52-3.98 mg/kg, Co 0.34-0.76 mg/kg and Ni ND are all in the above ranges. In fact the level of Fe in this study is in a higher range (16.5-146 mg/kg), compared to only one literature [17] from Turkey 159 mg/kg. The high value of Fe in this study is most probably resulted from the high concentration of Fe in the soil.…”
Section: Comparison Of Metal Levels Of the Present Study With Literatcontrasting
confidence: 74%
“…Also here the values from this study are in good agreement with those from literatures. If we look the values from the literatures [12][13][14][15][16][17] Fe is in the range 5.9-159 mg/kg, Cr 0.338-2.38 mg/kg, Mn ND to 8.4 mg/kg, Co ND to 0.8 mg/kg and Ni ND to 4.78 mg/kg. The levels of all the metals of this study are in the ranges from the literatures used, i.e.…”
Section: Comparison Of Metal Levels Of the Present Study With Literatmentioning
confidence: 99%
See 1 more Smart Citation
“…Quartey et al (2012) and Adotey et al (2009) also reported high variabilities in concentrations of these elements in tomato. The concentrations of Al recorded for all accessions were comparatively higher than values recorded for clover (23.6 mg/kg), oats (7.3 mg/kg), bean (5.1 mg/kg), green lentil (6.6 mg/kg), spinach (12.6 mg/kg), corn (11.90 mg/kg), red lentil (3.7 mg/kg) and rice (8.4 mg/kg) as reported by Hicsonmez et al (2012). On the other hand, Mn levels reported in okra (323 mg/kg); mango (326 mg/kg); carrot (2970 mg/kg); onion (1705 mg/kg); cucumber (392 mg/kg); tomato (418 mg/kg) and chilli pepper (236 mg/kg) by Ismail et al (2011) are higher than those reported in this study.…”
Section: Concentrations Of Ten Essential Elements In 22 Accessions Ofmentioning
confidence: 50%
“…The same element was weakly and negatively correlated with the rest of the elements except Ca which showed negative but moderate association. The strong associations between Ca and Cl as well as Mg are desirable as these elements are required in relatively large amount in the diets of humans (Hicsonmez et al, 2012). This suggests that it may be possible for the breeder to simultaneously select for higher concentrations of these pairs of elements in a breeding programme involving biofortification.…”
Section: Concentrations Of Ten Essential Elements In 22 Accessions Ofmentioning
confidence: 99%